Introduction to clinical neurology - Gelb, Douglas James, 1957- (New York, NY : Oxford University Press, 2024)
The sixth edition of 'Introduction to Clinical Neurology' continues to present a straightforward and systematic approach to diagnosing diseases of the nervous system. Extensively revised to reflect medical advances and now including supplementary tables for quick reference, this engaging textbook explains the neurologic diseases and presenting symptoms that clinicians are likely to encounter in daily practice. It also provides streamlined summaries of clinically relevant nervous system pathways to help non-neurologists deduce the site of dysfunction.
Previous edition: 2016.
Includes index.
Specialized.
Description based on online resource and publisher information; title from PDF title page (viewed on September 10, 2024).
Keywords: Neurology; Nervous system -- Diseases; Health and Wellbeing; Clinical & internal medicine